2021
DOI: 10.1155/2021/6650791
|View full text |Cite|
|
Sign up to set email alerts
|

MCU That Is Transcriptionally Regulated by Nrf2 Augments Malignant Biological Behaviors in Oral Squamous Cell Carcinoma Cells

Abstract: Objective. To clarify the role and molecular mechanism of mitochondrial calcium uniporter (MCU) in the malignant biological behaviors of oral squamous cell carcinoma (OSCC) cells through clinical and cellular experiments. Methods. Immunohistochemistry and qRT-PCR techniques were used to observe the expression of MCU, nuclear factor erythroid 2-related factor 2 (Nrf2), mitochondrial calcium uptake 1 (MICU1), and MICU2 in OSCC and normal tissues. After treatment with si-MCU, spermine, and/or sh-Nrf2, malignant b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…In previous studies, including our own, acute deletion or knockdown of MCU had significant effects on mitochondrial energy metabolism (Cardenas et al, 2016;Tosatto et al, 2016;Ren et al, 2017;Stejerean-Todoran et al, 2022). However, chronic deletion of MCU has been observed to not result in overt changes of basal mitochondrial metabolism (Pan et al, 2013;Kwong et al, 2015;Luongo et al, 2015;Hamilton et al, 2018;Koval et al, 2019;Wu et al, 2021). Discrepancies between chronic and acute MCU knockout/knockdown models is a recurring theme that might be explained by the activation of compensatory adaptations to maintain mitochondrial energy metabolism (Garbincius and Elrod, 2022).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In previous studies, including our own, acute deletion or knockdown of MCU had significant effects on mitochondrial energy metabolism (Cardenas et al, 2016;Tosatto et al, 2016;Ren et al, 2017;Stejerean-Todoran et al, 2022). However, chronic deletion of MCU has been observed to not result in overt changes of basal mitochondrial metabolism (Pan et al, 2013;Kwong et al, 2015;Luongo et al, 2015;Hamilton et al, 2018;Koval et al, 2019;Wu et al, 2021). Discrepancies between chronic and acute MCU knockout/knockdown models is a recurring theme that might be explained by the activation of compensatory adaptations to maintain mitochondrial energy metabolism (Garbincius and Elrod, 2022).…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, maintenance of quiescence and escape of hematopoietic stem cells (HSC) from quiescence requires mitochondrial Ca 2+ uptake (Resende et al, 2010;Umemoto et al, 2018;Ahumada-Castro et al, 2021;Paliwal et al, 2021). Inhibition of cell proliferation by MCU-KO is consistent with anti-proliferative effects of MCU suppression in cancer cells (Cardenas et al, 2016;Ren et al, 2017;Li et al, 2020b;Liu et al, 2020;Wang et al, 2020;Miao et al, 2021;Wu et al, 2021;, although this has not been universally observed (Curry et al, 2013;Hall et al, 2014;Tosatto et al, 2016;Young et al, 2022). Despite slower tumor growth in xenografts, proliferation in vitro of several breast cancer cell lines were independent of MCU (Tosatto et al, 2016), and it has been reported that stable deletion of MCU in HEK293T and HeLa cell lines resulted in enhanced cell proliferation (Young et al, 2022).…”
Section: Discussionmentioning
confidence: 77%
“…The MCU is a new proto-oncogene of OSCC, which is regulated by nuclear factor erythroid 2-related factor 2 (Nrf2) transcription. The MCU can enhance the proliferation of OSCC cells and inhibit apoptosis [ 142 ]. Dihydroartemisinin can repress the proliferation and migration of OSCC cells by inhibiting the expression of the MCU [ 143 ].…”
Section: The Relationship Between the Mcu And The Tumormentioning
confidence: 99%
“…Although these studies did not reveal the direct role of mitochondria in these processes, considering the importance of mitochondria in metabolism, mitochondria, undoubtedly also play a multitude of roles in OSCC. For example, mitochondrial calcium uniporter was strongly expressed in OSCC compared with normal tissues, and the downregulation of mitochondrial calcium uniporter expressly impaired the proliferation and migration of OSCC cells [ 40 ]. The oxidation of nicotinamide adenine dinucleotide (NADH), a lactate derivative from cancer-associated fibroblasts (CAFs), in the mitochondrial oxidative phosphorylation (OXPHOS) of OSCC cells could promote the proliferation of OSCC [ 41 ].…”
Section: Mitochondria and Osccmentioning
confidence: 99%